KAJIAN HUKUM TENTANG PAJAK HOTEL DI KOTA SAMARINDA DI TINJAU DARI PERATURAN DAERAH KOTA SAMARINDA NOMOR 4 TAHUN 2011 TENTANG PAJAK DAERAH - Taufik Indra Yoeshmana (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT The problem in this study is related to the Implementation of Tax Collection and Implications for Hotel Tax arrears according to the Samarinda City Regional Regulation Number 4 of 2011 concerning Regional Taxes and how the efforts of the Samarinda City Government in increasing Local Revenue (PAD) from Hotel Taxes in Samarinda City. The purpose of this study is to know and analyze the implementation of star hotel tax levies and the Implications on Hotel Tax arrears in Samarinda City Number 4 of 2011 regarding Regional Taxes and how the efforts of the Samarinda City Government in increasing Local Revenue (PAD) from Hotel Taxes in Samarinda City. The type of research used by the author in writing this scientific work is normative legal research that is legal research that examines law as aspects of theory, history, philosophy, comparison of structures, and composition of consistency, scope and material consistency, general explanation of article by article, formality and thebinding force of a law, as well as the legal language used. Starred hotel tax is a potential regional tax object as one of the sources of Regional Original Revenue (PAD) in Samarinda City, while the constraints are due to the lack of application of rules and sanctions for arrears related to hotel taxes in samarinda City Number 4 of 2011 concerning Regional Taxes namely not maximum income regional income that should be issued rules to be more stringent in increasing local tax levies and also the side effects that occur due to non-maximum rules that have been made into a problem that is arrears of tax payments made by taxpayers. In this case, the main objective of the regulation should be to increase regional income to the maximum and also provide overall decisiveness for taxpayers so that they are not in arrears in paying taxes, which are clearly stipulated in local tax regulations in Samarinda city. To increase Local Revenue (PAD) from star-rated hotel taxes, the city government needs to evaluate the Samarinda City Regional Regulation No. 4 of 2011 regarding Regional Taxes related to the maximum application of hotel tax collection rules and implement strict legal sanctions for tax arrears in all starred hotels which still does not obey or heed regional tax regulations so as to increase awareness and obedience of taxpayers so that retribution income will increase significantly Keywords: Hotel Taxes, Implementation of Rules, Tax Arrears Implications